The Impact of Methylenetetrahydrofolate Reductase Gene Polymorphisms on Iraqi Patients with Diabetic Nephropathy - A. Ali, Safa; A. Razak ALsharifi, Zainab; Abdul Majid Allawi, Ali (International Journal of Psychosocial Rehabilitation, 2020)
Diabetic nephropathy is a major cause of end-stage renal disease. Micro albuminuria is a term to describe a moderate increase in the level of urine albumin. It occurs when the kidney leaks mall amounts of albumin into the urine. The aim of this study was to investigate the influence of the C677T and A1298C polymorphisms of methylene tetrahydrofolate on the progression of chronic kidney disease in diabetic nephropathy of Iraqi patients to delay the deterioration in renal function. A hospital-based case-control study was performed. A total of 60 patients with diabetic nephropathy age (24-87) and 60 controls age (16-68) selected from nephrology center in Bagdad Teaching Hospital /Medical City from December 2017 until the end of August 2018, shows mean differences of study markers including (FBS, Blood urea, Serum creatinine and MTHFR) according to study group (micro albuminuria and control group). There were significant differences between means of all markers according to study group. in result conclusion Urinary biomarkers were significantly elevated in normoalbuminuric type 2 diabetic patients compared with nondiabetic control subjects and could be used as markers of diabetic nephropathy (DN) at a very early stage even before the development of micro albuminuria.